Zaprte po nedolžnem - Strajnar, Neža (Bogoslovni vestnik, 2023)
This article presents the fate of nuns who were unjustly accused and sentenced to imprisonment by the communist authorities in Slovenia after World War II. It includes information on how many nuns were imprisoned after the war, how long they served their sentences, and why. The treatment of religious women by the authorities, their treatment by the post-war judicial system, and the situation in women’s penal institutions are also described. Based on an analysis of the so-called prison files of the Archives of the Republic of Slovenia (Fond AS 1267, Republic Administrative Bodies and Institutions for the Execution of Sentences), the author concludes that their common characteristic is an upright attitude, firmness in faith, fidelity to one’s convictions and resistance to the repressive measures of the communist system.
Keywords: 20st.; 20th century; communism; komunizem; montirani sodni procesi; redovnice; religious sisters; staged trials; women’s prisons; ženske kazenske ustanove